Histopathological spectrum of hysterectomy specimens and its correlation with clinical diagnosis at a tertiary care centre - Dr. Abha Mishra; Dr. Poornima Mishra; Dr. Brig. Nikhilesh Kumar; Dr. Tanu Pandey; Dr. Shalini Srivastava; Dr. Mamta Dwivedi (Tropical Journal of Pathology and Microbiology, 2019)
Background: The uterus is the vital organ of female reproductive system which holds the fetus during pregnancy. Diseases of uterus has been broadly grouped into inflammatory, benign and malignant lesions. In our study hysterectomy specimens were studied and results were compared with their clinical diagnosis. Primary aim of our study was to correlate the histopathological features of the disease with its clinical diagnosis.Material & Methods: This was a retrospective study and included 277 hysterectomy specimens received over 2 year periods. Patient data was retrieved from the medical records and histopathology requisition form which included age, clinical findings, histopathological diagnosis, indication of hysterectomy and type of hysterectomy done. Histopathological findings from the cervix, endometrium, myometrium, ovaries and fallopian tubes of each and every hysterectomy specimen were noted.Result: A total of 277 cases were analyzed. Patient’s age ranged from 16 to 85 years thus included reproductive age group, perimenopausal and post- menopausal women. In our study most common indication for hysterectomy was abnormal uterine bleeding in 33.9 % cases followed by fibroid in 22% cases. The commonest chief complaint was heavy menstrual bleeding in 35.0% cases followed by abdominal pain in 32.5% cases. Majority of the patients were in 36-45year age group.Conclusion: Majority of the hysterectomy cases post - operatively were consistent with the clinical diagnosis, histopathological examination is still the gold standard test to diagnose and rule out malignancy and compulsory for all the surgical specimens.